A Grounded Theory of Experiential Group Training of School Counselors to Engage in Psychoeducational Group Lessons With First-In-Family Students. Issue 2 (3rd April 2019) - Finnerty, Sean; Luke, Melissa; Duffy, Jason T.
ABSTRACT: This study reports a qualitative grounded-theory investigation that explored school counselor trainees' experiences engaging in psychoeducational group lessons with first-generation college-going (first-in-family) high school students. As part of this semester-long, group-based experiential training, counselor trainees developed and implemented school counseling core curriculum lessons (psychoeducational groups) related to career and college exploration in 2 urban high school settings. Findings supported a theory that included 4 main factors: (a) Profession, (b) Student, (c) Group Field Experience, and (d) Self. Subthemes within the factors are explicated, and implications for future practice, training, and research are discussed.